Sorption efficiency of radioactive iodine compounds by nuclear-grade activated carbon - a review and processing of literature data - Mokili, Bandombele Marcel; Abdelouas, Abdesselam (Frontiers in Nuclear Engineering, 2025)
The sorption properties of I2 and CH3I on activated carbon were reviewed. The dependence of the sorption capacity on activated carbon of iodine and methyl iodide in air or effluent gas on the sampling operating conditions (temperature, relative humidity, linear velocity and bed length) was investigated. A compilation of experimental data on the sorption efficiency, penetration or decontamination factor of gaseous radioactive iodine species was carried out for nuclear-grade activated carbon. Non-linear surface fitting of experimental data of I2 and CH3I sorption efficiencies by activated carbon at different values of temperature and relative humidity shows that there are ranges of variation in both parameters where the removal capacity remains relatively constant. The values and associated uncertainties of the sorption efficiencies of I2 and CH3I by activated carbon cartridges with bed lengths of 25 and 50 mm were determined for different specified ranges of temperature, relative humidity and linear gas flow velocity. The Sorption Efficiency (SE) values can be used to determine the concentration of iodine radioisotopes in the gaseous effluent or ambient air in Bq/m3 from the results of radionuclide activity in the cartridge measured by gamma spectrometry.